FACTORS INFLUENCING MALAYSIAN YOUNG ADULTS’ ONLINE PURCHASE BEHAVIOUR - Engku Huda Mursyidah Engku Hassan Ashari; W. Nurfahizul Ifwah W.Alias; Rosfatihah Che Mat; Nik Suhaidi Nik Othman; Khamisah Abd Manaf; Sakinah Mat Zin (Journal of Islamic, Social, Economics and Development, 2023)
Many people have adopted online shopping as a way of life. The advancement of technology, as well as the ease of access to the internet, has resulted in the phenomenon of cross-border online purchases. Malaysian young adults contribute more than half of Malaysian internet users and they frequently use the internet to make online purchases. This implies that there are certainly factors that encourage young customers to engage in such behaviour. As a result, the objective of this research is to identify the factors that drive Malaysian young adults to buy online based on time consume, distance, and satisfaction. In this study, the Google Form survey method was used with 200 respondents and multiple response analysis. Most respondents stated that purchasing online saves time, effort, and energy. Meanwhile, most respondents believed that ordering online could save money on transportation costs. In terms of self-satisfaction, most respondents assumed that buying products online makes it easier for customers to get what they require. The purpose of this survey is to provide the public with an overview and understanding of the online purchasing phenomenon among Malaysian young adults.